Relation between serum beta-endorpin, neuropeptide Y and thyroid hormone in children with anorexia - He, Xu; Zhao, Hongling; Shi, Linxia; Wang, Wei; Yuan, Xiong (Journal of the Pakistan Medical Association, 2023)
The purpose of this study was to investigate whether serum B-endorpin and neuropeptide Y were associated with changes in levels of thyroid hormones in children suffering from anorexia. One hundred and five anorexic children admitted to Xianning City Central Hospital, China, from August 2019 to July 2021, were selected as case group, while 105 normal children were selected as normal control group. Serum B-endorpin and neuropeptide Y levels in the case group were lower than those in the normal control group (both P<0. 001), and serum triiodothyronine and thyroxine levels were also lower (both P<0. 001). Serum B-endorpin and neuropeptide Y levels in the case group were positively correlated with triiodothyronine and thyroxine. There is a reduced level of serum B-endorpin, neuropeptide Y, and thyroid hormones in anorexic children, and it is possible that they are connected and work together in regulating ingestion.